Prevalence and trends in mono- and co-infection of COVID-19, influenza A/B, and respiratory syncytial virus, January 2018–June 2023 - Lee, Min Kyung; Alfego, David; Dale, Suzanne E. (Frontiers in Public Health, 2023)
Objectives. To determine the impact of the COVID-19 pandemic on the overall prevalence and co-infection rates for COVID-19, Influenza A/B, and Respiratory Syncytial Virus in a large, national population. Methods. We conducted a retrospective review of 1,318,118 multi-component nucleic acid amplification tests for COVID-19, Influenza A/B, and RSV performed at Labcorp® sites from January 2018 to June 2023, comparing positivity rates and co-infection rates by age, sex and seasonality. Results. In 2021 – 2023, 1,232 (0.10%) tested positive for COVID-19 and Influenza A/B, 366 (0.03%) tested positive for COVID-19 and RSV, 874 (0.07%) tested for Influenza A/B and RSV, and 13 (0.001%) tested positive for COVID-19, Influenza A/B and RSV. RSV positivity rates were particularly higher in Q2 and Q3 of 2021 and in Q3 of 2022. Higher Influenza A positivity proportions were found in Q4 of 2021 and again in Q2 and Q4 of 2022. Influenza B positivity had been minimal since the start of the pandemic, with a slight increase observed in Q2 of 2023. Conclusions. Our findings highlight the need for adaptability in preparation for upper respiratory infection occurrences throughout the year as we adjust from the COVID-19 pandemic due to the observed changes in seasonality of Influenza and RSV. Our results highlight low co-infection rates and suggest heightened concerns for co-infections during peaks of the COVID-19, Influenza, and RSV may perhaps be reduced.